Therapeutic and Improving Function of Lactobacilli in the Prevention and Treatment of Cardiovascular-Related Diseases: A Novel Perspective From Gut Microbiota - Zhao, Xin; Zhong, Xinqin; Liu, Xiao; Wang, Xiaoying; Gao, Xiumei (Frontiers in Nutrition, 2021)
The occurrence and development of cardiovascular-related diseases are associated with structural and functional changes in gut microbiota (GM). The accumulation of beneficial gut commensals contributes to the improvement of cardiovascular-related diseases. The cardiovascular-related diseases that can be relieved by Lactobacillus supplementation, including hypercholesterolemia, atherosclerosis, myocardial infarction, heart failure, type 2 diabetes mellitus, and obesity, have expanded. As probiotics, lactobacilli occupy a substantial part of the GM and play important functional roles through various GM-derived metabolites. Lactobacilli ultimately have a beneficial impact on lipid metabolism, inflammatory factors, and oxidative stress to relieve the symptoms of cardiovascular-related diseases. However, the axis and cellular process of gut commensal Lactobacillus in improving cardiovascular-related diseases have not been fully elucidated. Additionally, Lactobacillus strains produce diverse antimicrobial peptides, which help maintain intestinal homeostasis and ameliorate cardiovascular-related diseases. These strains are a field that needs to be further investigated immediately. Thus, this review demonstrated the mechanisms and summarized the evidence of the benefit of Lactobacillus strain supplementation from animal studies and human clinical trials. We also highlighted a broad range of lactobacilli candidates with therapeutic capability by mining their metabolites. Our study provides instruction in the development of lactobacilli as a functional food to improve cardiovascular-related diseases.